2019
DOI: 10.1063/1.5096345
|View full text |Cite
|
Sign up to set email alerts
|

Spindle-like Fe3O4 nanoparticles for improving sensitivity and repeatability of giant magnetoresistance biosensors

Abstract: Magnetic labels are one of the most important components in giant magnetoresistance (GMR) biodetection systems and affect detection signals directly. Many researchers have improved the detection performance of GMR biosensors by optimizing the properties of their magnetic labels, including size, shape, coercivity, and magnetization. In most studies, magnetic labels are usually spherical, and there is little research involving alternative shapes. In this work, we prepared spindlelike Fe3O4 nanoparticles (NPs) by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…7(a), decreasing the effective magnetic field reduces the number of magnetic moments parallel to the H B . As the MNPs are located on the surface of the GMR chip, the voltage is reduced [22] due to the MNPs' stray field that increases the resistivity of the GMR chip. A higher concentration of MNPs, which indicates the larger number of MNPs attached to the GMR chip surface, generates a larger net stray field [42] that causes a more voltage reduction [22].…”
Section: B Sensor Performance In Detecting Mnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…7(a), decreasing the effective magnetic field reduces the number of magnetic moments parallel to the H B . As the MNPs are located on the surface of the GMR chip, the voltage is reduced [22] due to the MNPs' stray field that increases the resistivity of the GMR chip. A higher concentration of MNPs, which indicates the larger number of MNPs attached to the GMR chip surface, generates a larger net stray field [42] that causes a more voltage reduction [22].…”
Section: B Sensor Performance In Detecting Mnpsmentioning
confidence: 99%
“…To realize a simple system of GMR-based biosensors, previous works have employed the bare-die manufactured GMR chip for MNPs assay. Guan et al [22] reported the spindle-MNPs detection using bare-die GMR chip GF708 produced by Sensitec GmbH, Germany. With a similar chip, Zhang et al [23] quantified the Fe 3 O 4 MNPs concentration.…”
mentioning
confidence: 99%
“…human body of about 10 -13 T to a strong magnetic field of over 1000 T [1][2][3][4][5]. Many kinds of magnetic field sensors based on various physical effects have been developed and applied, including fluxgate sensors [2,[5][6][7], Hall sensors, giant magnetoresistance (GMR) sensors [8][9][10][11][12], superconducting quantum interference devices [3,[13][14][15][16][17], optical pump atomic magnetometers [18][19][20][21] and so on. With the rise of wearable devices, as the core component of wearable device systems, flexible magnetic sensors have been widely studied [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%